2021
DOI: 10.2147/rmhp.s299806
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Chromosomal Microarray Analysis for Detection of Copy Number Variations in Fetal Echogenic Bowel

Abstract: Background Fetal echogenic bowel (FEB) is associated with an increased risk of poor pregnant outcomes; however, karyotyping fails to detect copy number variations (CNVs) in FEB. This study aimed to evaluate the performance of chromosomal microarray analysis (CMA) for detection of FEB. Methods The medical records of 147 pregnant women with FEB recruited during December 2015 to December 2018 were retrospectively reviewed, and prenatal samples were collected for karyotypin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…27 Among the aneuploidies, hyperechogenic bowel could be related to trisomy 13, trisomy 18, monosomy X, Klinefelter's syndrome, chromosomal mosaicism trisomy, but trisomy 21 is the most common. [28][29][30][31][32] Literature data about chromosomal microarray analysis (CMA) anomalies are contrasting: Singer et al 33 34 In conclusion, the importance of CMA for prenatal diagnosis in fetal hyperechogenic bowel is still debated, and its use it is not mandatory.…”
Section: Chromosomal Anomaliesmentioning
confidence: 99%
See 1 more Smart Citation
“…27 Among the aneuploidies, hyperechogenic bowel could be related to trisomy 13, trisomy 18, monosomy X, Klinefelter's syndrome, chromosomal mosaicism trisomy, but trisomy 21 is the most common. [28][29][30][31][32] Literature data about chromosomal microarray analysis (CMA) anomalies are contrasting: Singer et al 33 34 In conclusion, the importance of CMA for prenatal diagnosis in fetal hyperechogenic bowel is still debated, and its use it is not mandatory.…”
Section: Chromosomal Anomaliesmentioning
confidence: 99%
“…Of these nine fetuses, in six cases CMA identified variants of uncertain significance (VOUS), and in the other cases pathological CNVs were diagnosed, related to the development of neurological and mental disorders and Hirschsprung's disease. The use of CMA in addition to karyotype plays an important role in the improvement of genetic prenatal diagnosis, although CMA could often find VOUS, but anyway both VOUS and pathological CNVs could present several manifestations among family members, ranging from completely normal phenotypes to full‐blown disease 34 …”
Section: Genetic Disordersmentioning
confidence: 99%
“…However, the results of the studies evaluating the significance of FEB were contradictory. [9][10][11] Several studies have suggested that FEB seemed to be a benign variant and the association between isolated FEB and fetal infection was uncommon. 9,12 However, most of those studies were carried out in isolated FEB, and the risk factors for poor pregnancy outcomes were not evaluated.…”
mentioning
confidence: 99%
“…[9][10][11] Several studies have suggested that FEB seemed to be a benign variant and the association between isolated FEB and fetal infection was uncommon. 9,12 However, most of those studies were carried out in isolated FEB, and the risk factors for poor pregnancy outcomes were not evaluated. Risk assessment of FEB is a prerequisite to carry an appropriate course of management.…”
mentioning
confidence: 99%
See 1 more Smart Citation